1994
DOI: 10.1177/000348949410301010
|View full text |Cite
|
Sign up to set email alerts
|

Pharyngocutaneous Fistula after Total Laryngectomy: Incidence, Cause, and Treatment

Abstract: Postoperative pharyngocutaneous fistula is a major complication of total laryngectomy that prolongs the short hospitalization of 2 to 3 weeks to many weeks or even months. It is a common complication that increases the morbidity and mortality of the procedure. In the Department of Otolaryngology of the Red Cross Hospital of Athens, 310 patients underwent total laryngectomy from January 1980 through December 1989. Twenty-eight patients developed a fistula (incidence 9%). The incidence, predisposing factors, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
74
2
6

Year Published

1998
1998
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(91 citation statements)
references
References 16 publications
9
74
2
6
Order By: Relevance
“…Several reports represent evidences incriminating some of these factors, while others do not arrive at similar conclusions (4,5,6,11,13,14,19).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several reports represent evidences incriminating some of these factors, while others do not arrive at similar conclusions (4,5,6,11,13,14,19).…”
Section: Introductionmentioning
confidence: 99%
“…Despite these improvements, many patients still experience recurrent disease requiring salvage surgery, most frequently as a total laryngectomy. It has been reported that occurrence of post-operative wound complication is affected by the treatment prior to salvage surgery, mainly irradiation (4,5,6). Moreover, chemotherapy has also been reported to increase post-operative wound complications in patients with advanced-stage resectable head and neck carcinoma (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…It is a complex, dynamic and systemic process, depending on the general health conditions of the patient with larynx neoplasm, and can be delayed by several intrinsic factors (age, preexistent diseases, radiotherapy, among others), which the nurse should identify in order to promote the continuity of the treatment process (9) . (10)(11)(12)(13)(14)(15)(16)(17)(18) .…”
Section: Results Of the Categories Extracted From The Studiesmentioning
confidence: 99%
“…Its development can double the average time of patient hospitalization, and consequently increase the costs (10,15) .…”
Section: Results Of the Categories Extracted From The Studiesmentioning
confidence: 99%
See 1 more Smart Citation